Pengembangan Aplikasi Perhitungan Prediksi Stock Motor Menggunakan Algoritma C 4.5 Sebagai Bagian dari Sistem Pengambilan Keputusan (Studi Kasus di Saudara Motor) - Pandu Pratama Putra; Andi Supriadi Chan (P3M Politeknik Negeri Bengkalis, 2018)
Limited company resources must be managed effectively and efficiently in order to guarantee corporate tax information technology information that will assist management within the company for every necessary process and reliable information. C 4.5 can be used to predict motor stock at Brothers Motor. the learning process that existed in the algorithm C 4.5 is preparing the data traning, calculate the root of the tree, and the partition process of the decision. The decision process will stop when all the records are in the N node that gets the same class, there are no attributes in the record that are partitioned again, there is no record in the empty network. The result of the average calculation algorithm algorithm C 4. Then the results of the calculation can be used for data processing. Data Mining uses the C4.5 algorithm then obtains a decision tree. Produce data obtained 12 rules (rules) in determining the prediction of preparation of motor stocks at Brothers Motor dealers.Key word: dss, algortm c 5.4,motorbike, dealer